Facile synthesis of polyethylenimine-modified sugarcane bagasse adsorbent for removal of anionic dye in aqueous solution - Nurul Balqis, Mohamed; Norzita, Ngadi; Wong, Syieluing; Noor Yahida, Yahya; Onn, Hassan; Inuwa, Ibrahim Mohammed; Opotu, Lawal Anako; Noorhalieza, Ali (Elsevier B.V., 2022)
Many studies have reported that surface modification of various type of materials by using polyethylenimine (PEI), usually necessitate to be combined with the crosslinkers, namely glutaradehyde, sodium tripolyphosphate, etc. The sugarcane bagasse (SB) is a fibrous agricultural waste derived from sugarcane stalks residue which has rich-cellulose content that makes it amenable to surface functionalization for tailored application. Thus, it is possible for SB material to modify by using solely PEI and eliminate crosslinking step. In this study, SB was used as supporting material for modified PEI to produce polyethylenimine-modified sugarcane bagasse (PmSB) for the adsorption of Reactive Black 5 (RB5) dyes from aqueous solution. The effects of contact time (60 – 300 min), adsorbent dosage (0.05 – 0.15 g); initial dye concentration (0.01 – 0.10 g/L), pH (5 - 9) and temperature (30 – 70 °C) were varied to evaluate the performance of the PSB under different experimental conditions. The kinetics study revealed that the adsorption experimental data fitted the pseudo second order model. The equilibrium adsorption data also fitted the Langmuir model with R2 of 0.99 and maximum monolayer capacity of 25 mg/g. The thermodynamic parameters suggest that the RB5 dye adsorption by PEI modified SB was spontaneous, exothermic and exhibited chemisorption. The adsorbent can be regenerated up to 4 cycles with the percentage dye removal greater than 80%). Therefore, the PmBS adsorbent has proven that the PEI is solely sufficient as modifying agents for SB material, even without an assistance of crosslinker reagents for removal of RB5 dye in aqueous solution.